Retweeting the News: Towards a formalized approach to the study of Twitter networks - De Grove, Frederik; D'heer, Evelien; Verdegem, Pieter (AoIR Selected Papers of Internet Research, 2016)
In this paper, we investigate the network processes behind the popularity metrics (i.e. retweet counts) for tweets coming from traditional news organizations. Twitter allows for the re-distribution and dissemination of mass media content, allowing it gain visibility online via retweets. This paper argues for two possible methodological approaches to understand the structural network processes behind retweets: (1) comparing parameter estimates against those from randomly generated networks with similar density and size and (2) comparing parameter estimates against those from randomly collected networks on Twitter. We outline the (expected) results for both procedures.